Pencegahan Pernikahan Dini Dalam Perspektif Hukum dan Kesehatan di Kelurahan Pammana - Andi Dadi Mashuri Makmur; Muharawati; Adam Chandra Kirana; Andi Muhammad Dika; Andri Ardian Aris; Elvira; fitrah (YP-SDI Lamaddukelleng, 2024)
Early marriage represents a significant challenge in the village of Pammana, with elevated rates of early marriage frequently attributed to social and economic pressures, coupled with a dearth of comprehension regarding the adverse consequences of early marriage. This article examines the efficacy of an educational approach that emphasises the importance of reproductive health and understanding of related legislation in preventing early marriage. The socialisation activities conducted at MTS Satap Nurul Ulum Pammana employed discussion and question-and-answer methods that facilitated active student participation in understanding the risks associated with early marriage and the importance of pursuing continued education. The results of the socialisation demonstrated an enhanced awareness among the students regarding the consequences of early marriage, as well as a heightened motivation to pursue higher education. It is imperative that continued education and strict law enforcement be implemented in order to reduce the number of early marriages in the future.